(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
The role of water resources in the economic and social development of the Surkhandarya region, which is located in an arid climate region, is highlighted, and the main attention is paid to the Topalang reservoir built in the northeastern region of the region and the work carried out in terms of the deployment and development of the production forces of the region, in the fields of electric power, and the safety of the dam, as well as, their importance in providing the population with clean drinking water is detailed. Key words: arid climate, water resources, production forces, hydrotechnical facilities, fresh water, economic and social development, recreation, electric power, Topalang reservoir, agriculture.